Bottom Interfacial Engineering for Methylammonium‐Free Regular‐Structure Planar Perovskite Solar Cells over 21%. Issue 8 (1st July 2021) - Leng, Shibing; Wang, Luyao; Wang, Xin; Zhang, Zhanfei; Liang, Jianghu; Zheng, Yiting; Jiang, Jinkun; Zhang, Zhiang; Liu, Xiao (Xiao); Qiu, Yuankun; Chen, Chun-Chao
Abstract : Formamidinium cesium (FACs) perovskite solar cells (PSCs) with the exclusion of methylammonium (MA) cations often have greatly improved device stability; however, their inferior performance compared with MA‐based devices has impeded the real application. Among various device engineering strategies, bottom interfacial engineering is a promising method to simultaneously achieve the passivation of interfacial defects and the crystallization control of perovskite. Herein, a simple and effective bottom interfacial design is presented to improve the efficiency and stability of FACs PSCs by capping o‐phenanthroline derivatives on the ZnO electron transporting layer (ETL). The most efficient modifier, 4, 7‐Dichloro‐1, 10‐phenanthroline (Cl‐phen), can improve the crystallinity of the perovskite film by chlorinated surface and passivate the defects of ZnO by reducing surface hydroxyl groups and oxygen vacancies. In addition, Cl‐phen modified ZnO shows better energy alignment with FACs perovskite and increases the built‐in electric field cascade by 80 mV. As a result, a champion device efficiency of 21.15% is obtained using ZnO/Cl‐phen bilayer ETL. The stability has also been improved using ZnO/Cl‐phen bilayer ETL, in which 91.5% of initial PCE is retained after 1500 h of storage at ambient environment (RH: 40–50%) without encapsulation. Abstract : This article introduces a bottom layer modifier for ZnO‐based methylammonium (MA)‐free perovskite solar cells. Chlorine‐containing phenanthroline derivative (Cl‐phen) reduces the surface oxygen defects, improves the charge extraction efficiency, and moderately increases the hydrophobicity to achieve a large grain size. A high‐performance solar cell with 21.15% is achieved. Its unencapsulated device maintains 91.5% of its stating PCE after 1500 h.